ANALISIS PERENCANAAN PPh 21 SEBAGAI UPAYA PENGHEMATAN BEBAN PPh BADAN PT ABC - Veronica Veronica; Purnamawati Helen Wijaya (Jurnal Paradigma Akuntansi, 2023)
ABC currently uses the Article 21 net income tax withholding method, where the burden of Article 21 Income Tax is borne by the company as well as allowances which include food allowances, pulses, transportation to add to take home pay, which causes Article 21 Income Tax to be large. The analysis technique used in this study is a comparative descriptive method. The results of this study indicate that the income tax planning effort 21 that can be done by PT ABC in achieving income tax savings in article 21 is to use the PPh 21 planning with the gross up method. The value of PPh 21 savings at PT. ABC if the company applies the gross up method is 0.06%, which means that the lower the effective tax rate, the lower the taxes it will bear.